Perspectives on dementia and family caregiving among the Oneida Nation of Wisconsin: Dementia care research (research projects; nonpharmacological) / Community care. (7th December 2020) - Lambrou, Nickolas H; Wyman, Mary F; Miller, Debra A; Thomas, Lauren; Strong, Lois; Summers, Marlene; Lassila, Patricia; Petri, Florence; Miller, Donald; Wheelock, Sunshine; Williams, Betty; Gleason, Carey E; et al.
Abstract: Background: Recent research indicates that prevalence of dementia amongst American Indian/Alaska Natives (AI/AN) is > 40% higher compared to Asian Americans and ∼18% higher than Whites. Yet, little is known about how AI/AN people conceptualize dementia, caregiving, and dementia care services. This study aimed to deepen understanding and highlight how the Oneida Nation of Wisconsin experiences and makes meaning of dementia, the family caregiver role, and home and community‐based service use. Method: Tenets of Community‐Based Participatory Research (CBPR) guided study design, recruitment, data collection and analysis. The study team conducted semi‐structured interviews with 22 Oneida Nation of Wisconsin participants. Audio recorded interviews were transcribed to text and coded thematically within and across participant narratives. A mixed‐methods approach was used to identify themes and to quantify participants' awareness of community dementia services. Result: Participants were a community sample of 22 Oneida Nation people in Northeastern Wisconsin. Mean participant age was 70.5 years; 16 participants identified as female and 6 as male. Of the entire sample, 77.3% of participants knew someone in the Oneida community with dementia, and 63.6% of participants identified as a caregiver (past or present) for a loved one with dementia, 82% were aware of monthly memory cafes, 43% were familiar with services provided by the dementia care specialist, and 75% were aware of the caregiver support group. Thematic analysis revealed commonalities in experiences of dementia and caregiving, including the value of family and community in caring for elders. Qualitative domains surrounding dementia diagnosis included: (1) Meaning making and stigma around "dementia" (2) The family caregiver experience, and (3) Awareness of and need for home and community based‐services. Conclusion: Exploratory qualitative and quantitative analysis revealed the nuances of how the Oneida Nation of Wisconsin conceptualizes dementia, the family caregiving role, and community‐based dementia care services. As participants shared their lived experiences with dementia, caregiving, and care resources, themes around community and cultural values emerged. Implications for Native communities, health care practitioners, and future research directions are discussed.